2001
DOI: 10.1007/pl00000902
|View full text |Cite
|
Sign up to set email alerts
|

Allometry of mammalian cellular oxygen consumption

Abstract: In the 1930s, Max Kleiber and Samuel Brody established that the interspecies correlation between mammalian body mass and metabolic rate (alphaM(0.75)) cannot be explained (solely) by whole body surface area (alphaM(0.66)) to volume ratios. Metabolic considerations must also be taken into account. Decreases in the proportion of visceral organ mass to whole body mass can account for some of the whole body metabolic differences. However, superimposed upon these anatomical differences, the metabolism of tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 47 publications
6
74
1
2
Order By: Relevance
“…Doses of PC-SPES used in our studies were calculated using an allometric exponent of 0.75 (based on whole body oxygen consumption) (Porter, 2001) and agree with the previous work of Kubota et al (2000). PC-SPES doses of 50 and 250 mg/kg/day in a 200-mg rat translates to approximately three and 13 capsules of PC-SPES per day, respectively, for a 70-kg human.…”
Section: Downloaded Fromsupporting
confidence: 71%
“…Doses of PC-SPES used in our studies were calculated using an allometric exponent of 0.75 (based on whole body oxygen consumption) (Porter, 2001) and agree with the previous work of Kubota et al (2000). PC-SPES doses of 50 and 250 mg/kg/day in a 200-mg rat translates to approximately three and 13 capsules of PC-SPES per day, respectively, for a 70-kg human.…”
Section: Downloaded Fromsupporting
confidence: 71%
“…MnSOD is localised exclusively within the mitochondrial matrix, so between-species differences in cellular mitochondrial abundance would influence scaling behaviour of any mitochondrial protein. Although the scaling of mitochondrial abundance with species MLSP should be negative (Porter 2001), and therefore further enforce the above correlation, we nonetheless measured CS activity as a proxy for mitochondrial number and found no relationship between brain CS activity and MLSP (data not shown). Also, MnSOD did not correlate with CS activity (data not shown), further indicating that the MnSOD correlation was not due simply to increased mitochondrial abundance in long-lived species.…”
Section: Resultsmentioning
confidence: 61%
“…Previous comparative studies of SOD have simply measured total activity, or KCN inhibitable activity, in tissue homogenates (Tolmasoff et al 1980;Sohal et al 1990;López-Torres et al 1993;Pérez-Campo et al 1994). As MnSOD is an exclusively mitochondrial enzyme and mitochondrial abundance scales negatively with species body mass in most tissues (Porter 2001), it is also necessary to take this into account when assessing relative MnSOD levels. Similar to CuZnSOD, we found no correlation between the activity of liver or heart MnSOD and animal MLSP.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared the scaling of metabolic rate of individual cells of endotherms (Porter 2001;West et al 2002). Some of the best data available come from Porter and colleagues (Porter andBrand 1995a, 1995b;Porter 2001) and Brown et al (2007), although the results of these two studies are totally opposed.…”
Section: Implications For Capillary Densities Cellular Metabolic Ratmentioning
confidence: 99%
“…Some of the best data available come from Porter and colleagues (Porter andBrand 1995a, 1995b;Porter 2001) and Brown et al (2007), although the results of these two studies are totally opposed. Porter and Brand measured the metabolic rates of isolated liver cells taken from mammals ranging in size from 20-g mice to 200-kg horses and found that they do indeed scale with mass Ϫ0.18 (Porter and Brand 1995b), close to the WBE expectation of mass Ϫ0.25 for freshly isolated cells.…”
Section: Implications For Capillary Densities Cellular Metabolic Ratmentioning
confidence: 99%